The Habitus of the People of Tempellemahbang Village Through Rencek Media in Contemporary Art - Rizka, Imawati; Dikdik, Sayahdikumullah; Dwi, Kurniawati (LP2M ISBI Bandung, 2024)
ABSTRACT The abundant teak wood waste in the village of Tempellemahbang, Blora Regency, which is called rencek, Rencek is a Javanese term that means the remains of pieces of wood that are no longer used and are identically used as firewood,was explored through a creative process by the author and used as a medium for creating paintings. Awareness of the exploration of rencek as a medium for painting is supported by the author’s aesthetic intuition and the habitus connection between the people of Tempellemahbang Village and the writer. As for the method of creating works, namely, the author collects & formulates problems related to the topic of the habitus of the people of Tempellemahbang Village, interprets the topic of the problem that the writer stretches to make it an idea for the work, the work design process starts from the medium used to the visualization of the work form, and the execution stage and work realization. In creating this work, the author is interested in and uses references to the work of several Indonesian artists Heri Dono, Amrus Natalsya, and Masmundari. The author explores using teak wood as a medium and produces five works with the title of work, among others; (1) Si Gadis Desa, (2) Tutup Telinga dan Teriaklah, (3) Blandong Kayu, (4) Raut Ekspresi Kami. The writer, who is a native of Tempelembang Village, is intrigued and wants to voice the issue of housing inconveniences in the environment by representing it in the form of works of art. The author uses the medium of rencek wood waste originating from industry. The author is interested in all the activities, expressions and responses of the surrounding community regarding the wood industry environment which can be expressed in contemporary works of art. Through this painting, it is hoped that it will be able to become a medium of artistic expression in expressing the expression of a society that is “oppressed” by capitalists. Keywords: Rencek, Contemporary Art, Decorative, Blora Regency